Record thermopower found in an IrMn-based spintronic stack - Sa Tu (Nature Portfolio, 2020)
Antiferromagnetic materials are potentially useful for spintronic applications. Here, the authors report high thermoelectric power value of 390 μV/K Seebeck coefficient in IrMn-based half magnetic tunnel junctions at room temperature.